Social Comparison dan Self-Esteem pada Mahasiswa Pengguna Instagram: Studi pada Mahasiswa Fakultas Psikologi UIN Raden Fatah Palembang - Sunah Pangestu Jati; Rizka Kurniawati; Dwi Despiana (Jurnal Ilmiah Psyche, 2026)
The increasing use of Instagram among university students has encouraged the tendency to engage in social comparison, a process of comparing oneself with others that may influence self-esteem. This study aimed to examine the relationship between social comparison and self-esteem among Instagram users at the Faculty of Psychology, Universitas Islam Negeri Raden Fatah Palembang. This study employed a quantitative approach with a correlational research design. The participants consisted of 300 students selected using a purposive sampling technique. Data were collected using the Iowa-Netherlands Comparison Orientation Measure (INCOM) to assess social comparison and the Rosenberg Self-Esteem Scale (RSES) to measure self-esteem. Data were analyzed using the Pearson Product Moment correlation test. The results revealed a significant negative relationship between social comparison and self-esteem (r = -0.305; p < 0.01). These findings indicate that the higher the tendency to engage in social comparison, the lower the students' self-esteem. The findings are expected to serve as a basis for promoting greater awareness among students regarding the importance of using social media more wisely to maintain and enhance their self-esteem